2011
DOI: 10.1007/s12185-011-0795-x
|View full text |Cite
|
Sign up to set email alerts
|

Radioguided lymph node biopsy of a chemoresistant lymph node detected on interim FDG PET-CT in Hodgkin lymphoma

Abstract: A 32-year-old male patient was diagnosed with nodular lymphocyte-predominant Hodgkin lymphoma. Staging FDG PET-CT detected a large right axillary lymph node conglomerate and splenic manifestation. Interim PET-CT following two cycles of ABVD chemotherapy revealed good metabolic response with the exception of a single axillary lymph node. A second ''interim'' PET-CT after two further cycles showed a similar result. A biopsy of the metabolically active non-palpable lymph node was performed using radioguided occul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
3
0
2
Order By: Relevance
“…The study showed that 3D FDG PET/CT may be a promising tool for further implementation of image-guided surgery. Györke et al [34] described a case of lymphoma in which an occult lesion localization method was used for radioguided biopsy of a chemoresistant lymph node detected with interim FDG PET/CT. Biopsy of the metabolically active, nonpalpable lymph node was performed with ultrasound guidance (Fig.…”
Section: Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that 3D FDG PET/CT may be a promising tool for further implementation of image-guided surgery. Györke et al [34] described a case of lymphoma in which an occult lesion localization method was used for radioguided biopsy of a chemoresistant lymph node detected with interim FDG PET/CT. Biopsy of the metabolically active, nonpalpable lymph node was performed with ultrasound guidance (Fig.…”
Section: Lymph Nodesmentioning
confidence: 99%
“…Several similarly enlarged but metabolically inactive further lymph nodes are present in right axilla ( G–I ). (Reprinted with permission from [34])…”
Section: Figmentioning
confidence: 99%
“…Second line treatment should not be initiated on the basis of a residual PET‐positive lesion alone. Biopsy is recommended to confirm the presence or absence of viable lymphoma and to assess for high‐grade transformation (Gyorke et al , ; Banzo et al , ). If biopsy is not performed, clinical follow‐up and early re‐assessment is recommended.…”
Section: Subsequent Imagingmentioning
confidence: 99%
“…Varios autores han descrito buenos resultados al ser utilizada como técnica de cirugía de rescate tras estudio PET-TAC, realizándose en algunas publicaciones igualmente confirmación previa con PAAF 10,15 . En otros trabajos la técnica ROLL fue aplicada satisfactoriamente como método de biopsia excisional con intención diagnóstica 6,16 .…”
Section: Discussionunclassified
“…No obstante, el material obtenido puede resultar insuficiente o el método tener escaso valor diagnóstico por la presencia de numerosas células reactivas y pocas células neoplásicas en la lesión, planteándose como primera opción la biopsia excisional 5,6 .…”
Section: Introductionunclassified